5
$\begingroup$

I'm trying to solve this system $$ \begin{align} x'&=x-3y+3z\\ y'&=-2x-6y+13z\\ z'&=-x-4y+8z \end{align} $$ must be reduced to a single equation I tried to express the x 3 and substitute in the other two but then I have not reduced y or z I can not understand how to solve it

Euler method can not be solved because it is written in the job to reduce to a single equation

$\endgroup$
1
$\begingroup$

I would look at the problem this way:

consider the vector $v = (x,y,z)^T$ and $ v' = (x',y',z')^T$. Then you can rewrite the problem like such:

$v'(t) = Av(t)$

where A is the matrix containing the coefficients of your functions. In your case:

$A :=\left( \begin{matrix} 1 &-3 & 3 \\ -2 & -6 & 13 \\ -1 & -4 & 8 \end{matrix} \right)$

Now you know that the solution must have the form $ v(t) = e^{At} \cdot c$ where $c \in \mathbb{R}^3$ is the vector with the constant values you could determine with given information about the functions. Assuming you know how the Jordan normal form works, you can rewrite this matrix as $ A = SJS^{-1}$. Then we have $ v(t) = e^{SJS^{-1}t} \cdot c$ and by using the definition of the exp function we get $ v(t) = S\cdot e^{Jt}\cdot S^{-1}\cdot c$. I will leave the matrix multiplication to you but I always thought that the $e^{Jt}$ was kinda tricky:

In your case:

$e^{Jt} = \exp\left( \begin{matrix} t & t & 0 \\ 0 & t & t \\ 0 & 0 & t \end{matrix} \right)$

You can divide this matrix into two separate ones: $I_n := \left( \begin{matrix} t & 0 & 0 \\ 0 & t & 0 \\ 0 & 0 & t \end{matrix} \right)$ and $N :=\left( \begin{matrix} 0 & t & 0 \\ 0 & 0 & t \\ 0 & 0 & 0 \end{matrix} \right)$

Then using $\exp(x+y) = \exp(x) \cdot \exp(y)$ you can now rewrite as such:

$e^{Jt} = e^{I_n} \cdot e^{N}$

and by taking a close look see that

$e^{I_n} = \left( \begin{matrix} e^t & 0 & 0 \\ 0 & e^t & 0 \\ 0 & 0 & e^t \end{matrix} \right)$

Almost done! But you must see that $N^k = 0 \forall k \geq 3$

That means you can calculate $e^N$ quite quickly and see that (if I calculated it correctly that is :) )

$e^N = \left( \begin{matrix} 1 & t & 0.5\cdot t^2 \\ 0 & 1 & t \\ 0 & 0 & 1 \end{matrix} \right)$

And therefore

$e^{Jt} = e^{I_n} \cdot e^{N} = \left( \begin{matrix} e^t & t\cdot e^t & 0.5\cdot t^2 \cdot e^t \\ 0 & e^t & t \cdot e^t \\ 0 & 0 & e^t \end{matrix} \right)$

And then you can finally see what your solutions must be by 'simple' matrix multiplication

$v(t) = S \cdot \left( \begin{matrix} e^t & t\cdot e^t & 0.5\cdot t^2 \cdot e^t \\ 0 & e^t & t \cdot e^t \\ 0 & 0 & e^t \end{matrix} \right) \cdot S^{-1} \cdot c $

I hope this could help you! If you are familiar with the Jordan normal form I think its a cool way to solve problems like this!

Best wishes,

Gustav

$\endgroup$
  • $\begingroup$ you have not even found the eigenvalues of $A!$ you think you can show how your methods applies to the matrix $A?$ $\endgroup$ – abel May 27 '15 at 20:16
  • $\begingroup$ thanks for the answer but I need to make these equations to one without the use of matrices and find the eigenvalues and eigenvectors for example should be able to $$x''+3x'+1=0$$ and then decided to substitute this equation in y and z solve them $\endgroup$ – Olya12 May 27 '15 at 20:24
1
$\begingroup$

Matrix approach: name the equations as (1), (2), (3). To reduce them into one, you have to do $$a\cdot (1) +b\cdot (2) +c\cdot (3)$$ such that the right hand side is exactly a multiple of the right hand side. That is $$(ax+by+cz)'=(a-2b-c)x+(-3a-6b-4c)y+(3a+13b+8c)z\\ =\lambda(ax+by+cz)$$

This makes it an eigenvalue problem. You need to solve for eigenvalue $\lambda$, then find the eigenvectors. The eigenvector will make a good set of $a,b,c$.

Another approach: (without using matrix)

$$2\cdot (3)-(2): 2z'-y'=-2y+3z\tag{4}\\ (1)+(3): x'+z'=-7y+11z\implies x'=-z'-7y+11z$$ Now equate this with (1): $$-z'-7y+11z=x-3y+3z\implies x=-z'-4y+8z \tag{5}$$

This equation can be used to eliminate the variable $x$. Taking the derivative of (5) gives $$x'=-z''-4y'+8z' \tag{6}$$ Plug (5) and (6) into (1): $$-z''+9z'-11z=4y'-7y\tag{7}$$ $$(7)-4\cdot (4): y=-z''+z'+z\tag{8}$$ Take derivative of (8): $$y'=-z'''+z''+z'\tag{9}$$

Now plug (8) and (9) into (7): $$2z'-3z=-z'''+z''+z'-2(-z''+z'+z)$$

This is the single ode for $z$.

$\endgroup$
  • $\begingroup$ thanks for the answer but I need to make these equations to one without the use of matrices and find the eigenvalues and eigenvectors for example should be able to $$x''+3x'+1=0$$ and then decided to substitute this equation in y and z solve them $\endgroup$ – Olya12 May 27 '15 at 20:26
  • $\begingroup$ @Olya12: I added another approach. Hope that helps. $\endgroup$ – KittyL May 28 '15 at 9:39

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.